Lipidomic Profiling of Human Milk Derived Exosomes and Their Emerging Roles in the Prevention of Necrotizing Enterocolitis. Issue 10 (22nd April 2021) - Chen, Wenjuan; Chen, Xiaohui; Qian, Yun; Wang, Xingyun; Zhou, Yahui; Yan, Xiangyun; Yu, Boshi; Yao, Shuwen; Yu, Zhangbin; Zhu, Jingai; Han, Shuping
Abstract : Scope: Human milk can prevent the development of necrotizing enterocolitis (NEC). Human milk is rich in cargo‐carrying exosomes that participate in intercellular communication. This study investigated the effects of term and preterm human milk‐derived exosomes, and elucidated their lipid expression profiles. Methods and Results: Milk from healthy mothers is collected who have delivered full‐term or preterm infants, and exosomes are isolated and quantified. Administration of term and preterm milk exosomes significantly enhances epithelial proliferation and migration in vitro, and ameliorates the severity of NEC in vivo. A total of 395 lipids are identified in term and preterm human milk‐derived exosomes. Bioinformatics analysis and western blotting reveal that top 50 lipids regulate intestinal epithelial cell function via the Extracellular‐Signal‐Regulated Kinase/Mitogen Activated Protein Kinase (ERK/MAPK) pathway. Conclusion: This study reveals for the first time the lipidomic complexities in exosomes derived from preterm and term milk. The results provide novel mechanistic insight on how human milk prevents the development of NEC. Abstract : Term and preterm human milk exosomes ameliorate the necrotizing enterocolitis (NEC) severity. Notably, the lipids detect in term and preterm human milk exosomes are almost the same. Bioinformatics analysis suggests potential regulatory role of the top 50 identified lipids in intestinal epithelial cell function via Extracellular‐Signal‐Regulated Kinase/Mitogen Activated Protein Kinase pathway. It provides a novel insight to understand the mechanism of human milk in preventing NEC.